First developments of the stoic theory of fate - Gómez Espíndola, Laura Liliana (Estudios de Filosofía, 2012)
The goal of this article is to clarify the first developments of Zeno, Cleanthes and Chrysippus’ Theory of Fate. In the course of the argumentation it will be clear that all of them considered Fate as identical to Divine Reason, the active principle of Nature responsible for moving and qualifying matter. On those grounds it will be argued, on the one hand, that they held that Fate is part of the intrinsic nature of the world and, on the other hand, that Fate has a universal scope, since all the movements and the qualitative states of the world, even in their smallest details, are produced by Divine Reason. Finally it will be shown that, according to the first developments of the three heads of the school, Fate has a fatalistic mechanism in the production of human life’s events.